1999
DOI: 10.1175/1520-0426(1999)016<0133:cocrww>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of COADS Release 1a Winds with Instrumental Measurements in the Northwest Atlantic

Abstract: The reliability of the Comprehensive Ocean-Atmosphere Dataset (COADS) Release 1a 2Њ monthly winds is tested by comparing it with instrumental measurements in the northwest Atlantic from 1981 to 1991. The instrumental dataset contains anemometer measurements of a very high homogeneity and quality, which were taken by six research sister ships with known anemometer heights in the northwest Atlantic. Special data processing was made with instrumental samples to provide compatibility with the COADS winds. Comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…averaging period; a possible increasing tendency to report gusts; changes in flow distortion effects due to changes in distribution of ship types, speeds, or recruiting country; and a changing contribution of errors from calculation of the true wind as the mean ship operating speed increases (along with ship-size) over time. Gulev (1999) discussed the impact of incorrectly calculating the true wind from the ship relative wind, particularly in locations where the orientation of the main shipping lanes coincides with the prevailing wind direction. For ships travelling in one direction across the ocean and returning by a slightly different route, these differences would not necessarily average to zero.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…averaging period; a possible increasing tendency to report gusts; changes in flow distortion effects due to changes in distribution of ship types, speeds, or recruiting country; and a changing contribution of errors from calculation of the true wind as the mean ship operating speed increases (along with ship-size) over time. Gulev (1999) discussed the impact of incorrectly calculating the true wind from the ship relative wind, particularly in locations where the orientation of the main shipping lanes coincides with the prevailing wind direction. For ships travelling in one direction across the ocean and returning by a slightly different route, these differences would not necessarily average to zero.…”
Section: Discussionmentioning
confidence: 99%
“…Sources of more homogeneous wind data could be used to validate the VOS winds and wind trends, such as research-vessel observations (Gulev, 1999;Smith et al, 2001), or buoy data. Moored buoy data are available over or near the continental shelves in the N. Pacific and N. Atlantic, beginning in the late 1970s at a few U.S. sites, and at increasing numbers of locations during the 1980s and 1990s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not account for a possible high bias in visual averages of an analogue anemometer dial. Errors in calculating true winds from platform relative winds could introduce consistent differences if shipping lanes are aligned with prevailing winds (Gulev, 1999). New logging systems mean that the occurrences of such errors should reduce over time.…”
Section: Possible Sources Of Residual Inhomogeneitymentioning
confidence: 99%
“…Inhomogeneities occur for many reasons, including: different observing methods (Quayle, 1980;Peterson and Hasse, 1987;Cardone et al, 1990;Wilkerson and Earle, 1990;Kent et al, 1993Kent et al, , 1998Lindau 1995a;); systematic changes in measurement height (Cardone et al, 1990); airflow distortion over the ship (Dobson, 1981;Yelland et al, 2002;Moat et al, 2005); different averaging times and methods (Dobson, 1981;Pierson, 1983;Gilhousen 1987;Taylor et al, 2002); and the effect of environmental conditions (Dobson, 1981;Kent et al, 1993). Other sources of observational error include: differences from nominal observing time; the anemometer type, calibration, and location; errors in calculation of true wind from the relative wind (Kent et al, 1993;Gulev, 1999;Smith et al, 1999); rounding artefacts; and for Beaufort winds, the stage of development of the waves. Researchers have studied the relationship between Voluntary Observing Ship (VOS) winds and pressures and have concluded that in some cases the pressure and wind trends are consistent (Inoue and Bigg, 1995) and in some cases inconsistent (Posmentier et al, 1989;Ward and Hoskins, 1996).…”
Section: Introductionmentioning
confidence: 99%